(NgIDROFIZI^ESKIE ISSLEDOWANIQ kARIBSKOGO MORQ (B/s - (NbULGAKOW(B, (NnIKOLAJ pETROWI^s; (NdOCENKO(B, (Ns(B. (Nf(B.s; (NkU[NIR(B, (Nw(B. (Nm(B.s; (NbUKATOW(B, (NaLEKSEJ eWTIHIEWI^s; (NuKRAINSKIJ MORSKOJ GIDROFIZI^ESKIJ INSTITUTs ((NkIEW (B:s (NnAUK(B. (NDUMKA(B,s, 1991)
(NbIBLIOGR(B.: (NS(B. 182-187 s
(Nan ussr(B, (NmOR(B. (NGIDROFIZ(B. (NIN(B-(NTs
Keywords: (NgIDROFIZI^ESKIE ISSLEDOWANIQ MORSKIE (B- (NkARIBSKOE MOREs